Pravastatin attenuates allergic airway inflammation by suppressing antigen sensitisation, interleukin 17 production and antigen presentation in the lung. Issue 1 (3rd October 2008) - Imamura, M; Okunishi, K; Ohtsu, H; Nakagome, K; Harada, H; Tanaka, R; Yamamoto, K; Dohi, M
Abstract : Background: Statins are widely used to treat hyperlipidaemia. Their immunosuppressive effect has recently been confirmed in various immune mediated disease models. However, relatively few studies have been conducted on allergic inflammation, so the precise mechanisms of their actions against allergies have not been fully clarified. On the other hand, the role of interleukin (IL)17 in immune responses has been recently highlighted, but whether statins affect IL17 production has not been well studied. The effect of pravastatin on allergic airway inflammation in a mouse model was examined to elucidate the mechanism of action, focusing on its effect on IL17 production. Methods: BALB/c mice were immunised with ovalbumin (OVA) and then challenged with OVA aerosol. Pravastatin was delivered by intraperitoneal injection during either sensitisation or the challenge. Results: When delivered during systemic sensitisation, pravastatin suppressed OVA induced proliferation and production of Th2 type cytokines such as IL5 in spleen cells ex vivo and in vitro. IL17 production was also suppressed. Furthermore, pavastatin delivered during the inhalation of OVA attenuated eosinophilic airway inflammation, OVA specific IgE production in serum and OVA induced IL17 production in the thoracic lymph node. We also found that pravastatin attenuated the antigen presenting capacity of CD11c + cells obtained from the OVA challenged lung. Conclusion: Pravastatin suppresses the systemic sensitisation to allergen with downregulation of IL17 production. It also suppresses an ongoing immune response in the airway partly by suppressing antigen presentation in the lung. Therefore, statins could be a novel therapeutic option for treatment of asthma.